ON THE BEHAVIOR OF MARINE CRUSTACEANS IN AN ELECTRICAL FIELD OF ALTERNATING CURRENT - BISWAS, K P (Fishery Technology, 2025)
The minimum flow of current essential to produce electronarQcosis and fixation in marine crustaceans, Metapenaeus affinis1 Parapenaeopsisstyli(era1 Panulirus ornatus and Neptunus sanguinofentus inan AC field of specific strength varied with the lengths of animalstested, except in case of the last one where the increase in size ofanimals showed no significant effect on the effective period fordifferent reactions. M. affinis in interrupted AC required thresholdpulses for narcosis and fixation, which varied inversely with thelength of the organism. Animals ~mbjected to current of highereffective period required Ion ger time for recovery in interrupted ACof 50 cfs. The period for narcosis and recovery of M. af(tnis did notvary significantly with repeated stimulations on the same organism